Postoperative symptom monitoring with ePROs in an academic public hospital. Issue 28 (1st October 2022) - Mody, Gita N; Thompson, Jillian C; Williams, Brittney M; Shrestha, Sachita; Bryant, Mary-Catherine; Bright, Annie; Nevison, Julia; Cox, Chase; Perez, Miriam; Newsome, Bernice; Hill, Lauren; Deal, Allison Mary; et al.
Abstract : 264 Background: Postoperative symptom burden is high in surgical oncology patients. Electronic patient-reported outcome (ePRO) remote monitoring systems are rapidly proliferating and have the promise of improving care. However, implementation in diverse practice settings is understudied. More information on ePRO participation may determine addressable barriers. Methods: Patients presenting to the Multidisciplinary Thoracic Oncology Program for surgery were prospectively enrolled. ePROs assessing common postop symptoms and functional impairments were administered via a web-based platform daily for 14 days and then weekly until 3 months post-discharge. Automated reminders were provided by email. Phone calls were made for 2 consecutive missed ePROs. ePRO participation levels were categorized as high (> 80%), medium (50-80%), low (1-49%), and none. Patient characteristics were examined by participation level via Fisher's exact and Kruskal-Wallis tests. Results: From 2020-2022, 202 patients were recruited to participate, and 113 (56%) agreed. There were no differences in demographics of agreed vs. declined. 99 patients initiated ePROs after discharge. Mean age was 60.5 years (sd 13.4), 37.8% were male, 72.5% were White, and the majority (64%) had lung resection. Patients participated in ePROs for an average of 82 days (sd 24) before discontinuing. Overall, 57.7% (1383/2397) of delivered surveys were completed; response rates were lowest in week 1 (48%) and highest in week 7 (71%). Participation levels are described in Table. Married/partnered patients were significantly more likely to have high levels of participation (p = 0.003), and those who regularly used a computing device almost reached significance (p = 0.057). Age, gender, race, employment, email/internet use, financial status, and quality of life did not vary across ePRO participation levels. Conclusions: Monitoring symptoms with ePROs after discharge from thoracic surgery is feasible in a large academic public hospital. Participation levels in ePROs are lower immediately after discharge, when symptomatic complications drive the highest rates of readmissions. This suggests an opportunity to improve ePRO implementation during the post-acute period when intensive monitoring is desired and in patients who are not partnered or are less frequent device users. As length of stay and readmissions are increasingly targeted for expenditure reduction in academic inpatient settings, it is paramount to design and implement systems to effectively monitor at-risk patients. Clinical trial information: NCT04342260. Percent of patients within each ePRO participation level by time since discharge. Post-discharge timing High (> 80%*) Medium (50-80%*) Low (1-49%*) None (0%*) Total Daily survey delivery: Day 1-7 34% 27% 17% 22% 100% Day 8-14 37% 28% 13% 22% 100% Weekly survey delivery: Week 3-4 64% 10% 0% 26% 100% Week 5-8 51% 25% 6% 18% 100% Week 9-12 49% 20% 7% 24% 100% *% of post-discharge ePRO surveys completed.